Anthropometric, body composition, and morphological lower limb asymmetries in elite soccer players: A prospective cohort study - Mala, L.; Maly, M.; Cabell, L.; Hank, M.; Bujnovsky, D.; Zahalka, F. (International Journal of Environmental Research and Public Health, 2020)
The aim of this study was to identify and compare parameters related to anthropometry, body composition (BC), and morphological asymmetry in elite soccer players in nine age categories at the same soccer club (n = 355). We used a bio-impedance analyzer to measure the following indicators of BC: body height (BH); body mass (BM); relative fat-free mass (FFMr); percentage of fat mass (FM); and bilateral muscle mass differences in the lower extremities (BLD?). Age showed a significant influence on all parameters observed (F64,1962 = 9.99, p = 0.00, ? = 14.75, ?2p = 0.25). Adolescent players (from U16 through adults) had lower FM values (<10%) compared to players in the U12-U15 categories (>10%). The highest FFMr was observed in the U18 category. Players in the U12 and U13 categories showed more homogenous values compared to older players. With increasing age, significantly higher FFMr was observed in the lower extremities. An inter-limb comparison of the lower extremities showed significant differences in the U17 category (t27 = 2.77, p = 0.01) and in adult players (t68 = 5.02, p = 0.00). Our results suggest that the end of height growth occurs around the age of 16 years, while weight continues to increase until 20 years. This increase is not linked to decreasing FM, nor to the FFMr, which remains stable. We found morphological asymmetries between limbs in players of the U17 category and in adult players.